Application to fixed point theory of -Geraghty Pata proximal contractions - Alam, Khairul Habib; Rohen, Yumnam; Albargi, Amer Hassan; Hussain, Aftab (Fixed point theory and algorithms for sciences and engineering, 2025)
In this paper, we introduce the concepts of -Geraghty Pata proximal contractions and their weak ϕ -variants, which generalize and unify several well-known contraction conditions in fixed point theory. By integrating the ideas of Geraghty and Pata contractions with the framework of α − θ -proximal admissibility, we establish best proximity point theorems for both single-valued and multivalued non-self mappings in metric spaces. Furthermore, we extend our results to the context of coupled fixed points and partially ordered metric spaces, thus broadening their applicability. The presented theorems generalize a range of existing results and offer a more flexible setting for analyzing nonlinear problems. We also include a concrete application to fractional differential equations and provide illustrative examples to demonstrate the effectiveness of our results.